Atividade enzimática oxidativa dos fungos amazônicos Pleorotus sp (F-31), Lentinus crinitus e Hexagonia glabra - Santos, Jucileuza Conceição dos (2009)
This study it find for to determine physiological parameters of growth and enzymatic activity of three Amazonian fungi. The used fungi had been (Pleorotus sp (F-31), Lentinus crinitus and Hexagonia glabra), gotten of the collection of fungi of the MBT. The evaluation of the radial growth in tests of plate of Petri with the following nutrition ways: BDA, Malte and Jerimum. The evaluation of the growth also was carried through in different concentrations of the atrazine herbicides to verify the potential of the fungi for degradation of this herbicides. The enzymatic activity was determined for phenoloxidase total, laccase and peroxidase. The micelial growth in different nutrition ways, pH and temperature had shown that different the tested fungi had presented behavior, influenced for the temperature, pH and half nutrition All the tested fungi had increased its enzymatic production of tested oxidative enzymes in the presence of tween-80. Hexagonia glabra produced more about 10 times laccases of what the other fungi tested in the concentration of 1,5 g.L -1 of not-ionic surfactante Tween, whereas Pleorotus sp (F-31) was what it presented the lesser enzymatic activity for all the enzymes. Fungi Hexagonia glabra was what it presented percentile greater of fungi mass in a bigger period of the experiment. Fungi Pleorotus sp (F-31) and Hexagonia glabra reveal capable to grow, with reasonable biomass in way of culture supplemented with different concentrations of atrazine demonstrating the possible potential of these fungi for degradation of this herbicides.